Member loyalty and WOM in co-operative and mutual enterprises. Issue 3 (10th June 2019) - Mazzarol, Tim; Soutar, Geoffrey; Mamouni Limnios, Elena
Abstract : Purpose: The purpose of this paper is to present findings from a large-scale survey of members of co-operative and mutual enterprises (CMEs) that examines the factors influencing members' intentions to remain loyal to the enterprise and to provide word of mouth (WOM). Design/methodology/approach: A model was suggested and tested to examine the interrelationships between constructs measuring emotional, functional and financial value, affective and continuance commitment, intention to remain loyal to a CME and WOM communication. A large sample was drawn from a range of co-operative and mutual enterprises, and the suggested model was estimated using a partial least squares approach. Findings: Significant relationships were found between all constructs. However, emotional value and affective commitment were found to have particularly strong relationships. Emotional value had a strong influence on both affective and continuance commitment, while affective commitment had a strong influence on loyalty and WOM. Originality/value: This paper provides empirical support for suggestions about the factors that influence member loyalty within CMEs and the relative importance of non-financial motivations. It also provides a strong foundation upon which directors and executive managers of CMEs can build more effective member marketing and communications strategies.